Experimental Research Dalam Penelitian Pendidikan - Rahayu, Meiliza Suci; Siroj, Rusdy A; Afgani, M Win (Jurnal Ilmiah Wahana Pendidikan, 2024)
Experimental research is a type of research that aims to prove the effect of a treatment on the consequences of that treatment. Arikunto explained that by means of experiments, researchers deliberately generate an event or situation, then examine the consequences, in other words, experimental research is a way to look for a cause-and-effect relationship between two factors. Experimental research generally places more emphasis on fulfilling internal validity, namely by controlling the influence of factors outside the experiment that can influence the experimental results. The factors that can threaten the internal validity of an experimental research result include: (1) History, (2) Maturation, (3) Testing Effects, (4) Instrumentation, (5) Selection, (6) Mortality. Ary, et al, determined that in experimental research there are three important elements as the main characteristics of carrying out experiments, namely: The existence of control, The existence of manipulation, The existence of observation. According to Tuckman, there are 4 types of experimental research, namely Pre-Experimental, True Experimental, Factorial and Quasi Experimental. Meanwhile, Sukmadinata's book states that experimental research based on variations consists of pure experimental research (True Experimental), Quasi Experimental (Quasi Experimental), Weak Experimental (Weak Experimental), and Single Subject Experiment (Singel Subjectl).